PREVALENCE OF COCCIDIOSIS IN GOATS IN NAGPUR REGION OF MAHARASHTRA - Bagde, Varsha; Jumde, Pratibha; Bansod, Shraddha; Shende, Kavita; Maske, D K (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A survey on the prevalence of coccidiosis in goats was conducted in two different localities viz., Ramtek and Katol Tahsils of Nagpur district of Maharashtra during the year 2008-2009. A total of 1500 goats were examined for coccidial infection of which 940 samples (62.66%) were found to harbour the Oocysts of Eimeria sp. infection. Among 375 kids examined, 230 samples (61.33%) were found infected with coccidiosis.